A Quality assessment of cold dried chicken slices during storage in different packages and temperatures - Elif Aykın Dinçer; Mustafa Erbaş (Agricultural and Food Science, 2023)
In this study, dried chicken slices were packaged in MAP (modified atmosphere packaging) and AP (atmospheric packaging), and stored at 4 °C and 25 °C. The CO2 content of MAP packaged samples decreased as the storage temperature and time increased. The slices exhibited lower aw values when they were packaged in AP at 25 °C. The pH increased from 6.1 to 6.2, 2-thiobarbituric acid reactive substances (TBARS) increased from 10.6 to 37.3 µmol MDA kg-1, and non-protein nitrogen (NPN) increased from 4.9 to 5.3 g 100 g-1 in MAP for 90 days of storage. The microbiological quality of the samples was assessed by enumerating total aerobic mesophilic bacteria (TAMB), total psychrophilic bacteria (TPB), Micrococcus/ Staphylococcus, lactic acid bacteria (LAB), Enterobacteriaceae and yeast-mold, and was higher in the sample stored in MAP at 4 °C. Moreover, the sensory quality was determined by sensory evaluation with a 9-point hedonic scale. When the sensory and microbiological qualities were evaluated together, the shelf lives of the samples were determined to be 90 days at 4 °C and 75 days at 25 °C for MAP and 45 days at 4 °C and 30 days at 25 °C for AP. It could be concluded that the cold dried chicken slices can be stored in MAP for 90 days without much change in physicochemical, microbiological, and sensory quality.